Increased expression and altered subcellular distribution of PKC-delta in chronically hypoxic rat myocardium: involvement in cardioprotection - Neckár, Jan; Marková, Irena; Novák, Frantisek; Nováková, Olga; Szárszoi, Ondrej; Ost'ádal, Bohuslav; Kolár, Frantisek (American journal of physiology. Heart and circulatory physiology, 2005)
We examined the role of protein kinase C (PKC) in the cardioprotective mechanism induced by long-term adaptation to chronic intermittent hypoxia. Adult male Wistar rats were exposed to hypobaric hypoxia of 7,000 m for 8 h/day, 5 days/wk; the total number of exposures was 24-32. A control group was kept under normoxic conditions. Western blot analysis of PKC isoforms-delta and -epsilon was performed in the cytosol and three particulate fractions of left ventricular myocardium. Infarct size was determined in open-chest animals subjected to 20-min coronary artery occlusion and 3-h reperfusion. The PKC inhibitors chelerythrine (1 or 5 mg/kg) or rottlerin (selective for PKC-delta isoform; 0.3 mg/kg) were administered intravenously as a single bolus 15 min before ischemia. Chronic hypoxia had no effect on the expression and distribution of PKC-epsilon. The relative amount of PKC-delta increased in the cytosol and nuclear-cytoskeletal, mitochondrial, and microsomal fractions of chronically hypoxic myocardium by 100%, 212%, 237%, and 146%, respectively, compared with corresponding normoxic values. Chronic hypoxia decreased the size of myocardial infarction (normalized to the area at risk) by about one-third on the average (P < 0.05). Both doses of chelerythrine tended to reduce infarction in controls, and only the high dose completely abolished the improvement of ischemic tolerance in hypoxic hearts (P < 0.05). Rottlerin attenuated the infarct size-limiting effect of chronic hypoxia (P < 0.05), and it had no effect in controls. These results suggest that chronic intermittent hypoxia-induced cardioprotection in rats is partially mediated by PKC-delta; the contribution of other isoforms remains to be determined.
Keywords: Hematocrit; Protein Kinase C-epsilon; Chronic Disease; hematokrit; reperfuzní poškození myokardu; Heart Rate; krysa rodu Rattus; Hypoxia; zvířata; infarkt myokardu; Myocardial Reperfusion Injury; proteinkinasa C-epsilon; potkani Wistar; hypoxie; Rats, Wistar; krevní tlak; Male; srdeční frekvence; Protein Kinase C-delta; chronická nemoc; Myocardial Infarction; proteinkinasa C-delta; Protein Kinase C; Heart Ventricles; inhibitory enzymů; Rats; myokard; proteinkinasa C; Animals; Myocardium; mužské pohlaví; Blood Pressure; Enzyme Inhibitors; srdeční komory